DETERMINATION OF SUCRALOSE IN TABLE TOP SWEETENERS PREPARATION BY MEANS OF COLORIMETRY APPLYING ANTHRONE COLOR REAGENT - Musfarli
Background: Sucralose is a food additive of artificial sweeeteners functional class with a sweetness level of 600 times sweeter than sucrose and ADI (Acceptable Daily Intake) value of 0-15 mg/ kg body weight/ day. From the point of view of risk analysis, the exposure assessment of such food additive is of high priority to be performed. For this purpose, an analytical method for determination of sucralose in different food product is necessary. The aim of this research was to obtain an analytical method for determination of sucralose in table top sweeteners can be applied for routine determination of that food additive. Method: Determination of sucralose was initiated by preparative separation of sucralose from other components applying Thin Layer Chromatography (TLC). Sucralose was then reacted with anthrone in acidic condition resulting in the formation of colored product, measurable with a visible spectrophotometer. The method was validated and then applied for determination of sucralose in table top sweeteners. Result: Sucralose was succesfully separated from other components with a retardation factor of 0.83. After reaction with anthrone reagent, bluish-green solution was obtained and subsequently measured spectrophotometrically resulting in a spectrum with maximum wave length of 622 nm. Validation parameters such as linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy and precision were determined. Two calibration curves were prepared from standard solution of sucralose and standard solution of sucralose obtained from TLC separation. Both calibration curves were linear over the range of 10 –70 µg/mL. The first calibration curve has regression equation of y = 0.0081x – 0.0072 with correlation coefficient (r) of 0.99967, while the second one with the regression equation of y = 0.0059x –0.0028 with correlation coefficient (r) of 0.99967. The limits of detection (LOD) and limits of quantification (LOQ) which were statistically calculated from the first calibration curve were 1.36 dan 3.86 µg/mL. The precision of the method, stated as RSD of repetitive determination, were 2.306, 2.263 and 2.127% for intra-day variation, while those of inter-day variation were 2.523, 2.285 and 2.265%. The recoveries of sucralose standard addition method from table top sweeteners were 98.954 - 108.138%. The concentration of sucralose in four commercial table top sweeteners preparation were 104.2, 101.0, 104.9 and 357.3% of label claim, respectively. Based on overall results, it was concluded that an analytical method for determination of sucralose in table top sweeteners was successfully obtained.